A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia - Kurita, Takaki; Nishikawa, Kanto; Matsui, Masafumi; Hikida, Tsutomu (Zootaxa, 2017)
A new species of Asian rock gecko, genus Cnemaspis, is described from Padawan, western Sarawak, Malaysian Borneo. The new species forms a clade with C. paripari and C. nigridia of the C. nigridia group in a mitochondrial DNA phylogeny and is similar to them morphologically in some characters such as caudal scalation. It differs from the other Asian Cnemaspis species in its unique combination of snout–vent length (up to 62.7 mm), 4–9 precloacal pores in males, keeled subcaudals with an enlarged, smooth, median row, presence of ventrolateral caudal tubercles, and coloration (head and upper flanks dark-yellow; anterior portion of tail black; posterior portion of tail white with black, paravertebral blob). Phylogenetic relationships within the C. nigridia group and the distributional ranges of species within the group suggest allopatric speciation by geographic isolation.